(untitled) (Journal of Oriental Studies, 2019)
In this article it is examined the general situation of the language policy of Kazakhstan, the problem of the state language and the main directions of the language policy of Kazakhstan. During the years of independence, no ethnic group in Kazakhstan lost its language. Kazakh land united more than a hundred ethnic groups. Of course, the main factor in uniting ethnic diversity into one nation is the state language – the Kazakh language. The knowledge of the state language and mastering several foreign languages means increasing the personal competitiveness of citizens of the country. Each Kazakh citizen is obliged to master at least three languages: Kazakh, Russian and English at the state level. At the same time, in this work, it is stated that young people have learned about the values associ- ated with the formation of a new language situation in the context of the independence of Kazakhstan and the new language policy. In this article it is described that trilingualism within the meaning of multilingualism is certainly enriching the people. Researchers describe the privileges of multilingualism, multilingualism has been discussed as an indicator of the formation of a global mentality. This means not only being able to speak several languages, but also a special kind of thinking to inculculate the cultural values of several civiliza- tions. Training of teachers of disciplines in English in higher educational institutions of the republic is a guarantee of the future. The goal is clear – the creation of advanced systems of distance-learning and online-learning, to actively develop the state language and trilingualism. Key words: Kazakh language, state language, language policy, multilingualism, bilinguaism, trilin- gualism.